TARI TULAK BLA DALAM KARYA LUKIS EKPRESIONISME - Hedi Chandra; Lisa Widiarti (Universitas Negeri Padang, 2020)
The purpose of making this final work of painting is to visualize the value of the traditional Tulak Bla dance with an expressionist style while maturing the technical skills of painting and deepening the concept of work. The method used in the final work is the preparation stage, the elaboration stage, the synthesis stage, the concept realization stage, and the completion stage. So that ten works were created that visualize the traditional Tulak Bla dance procession with the following titles: the first work,